Fluorescence, in microscopy and imaging (Global Journal of Science Frontier Research, 2012)
This is a swift report on fluorescence and its application as a tool in imaging and microscopy; to properly comprehend this subject, with the aid of the Jablonski diagram, brief descriptions and discussions are given on fluorescence; rhodamine 6G homo-FRET reaction is considered from which both the absorption and emission spectra are drawn on a graph. Additionally, the wealth of applications of fluorescence imaging techniques such as Fluorescence Lifetime Imaging Microscopy (FLIM) and Fluorescence Polarisation and Anisotropy techniques are considered. Applications of molecular imaging techniques in cell biology and medical science are mentioned.
Keywords: rhodamine; Fluorescence; Polarisation; Anisotropy